A Self‐Consistent Fault Slip Model for the 2011 Tohoku Earthquake and Tsunami. Issue 2 (7th February 2018) - Yamazaki, Yoshiki; Cheung, Kwok Fai; Lay, Thorne
Abstract: The unprecedented geophysical and hydrographic data sets from the 2011 Tohoku earthquake and tsunami have facilitated numerous modeling and inversion analyses for a wide range of dislocation models. Significant uncertainties remain in the slip distribution as well as the possible contribution of tsunami excitation from submarine slumping or anelastic wedge deformation. We seek a self‐consistent model for the primary teleseismic and tsunami observations through an iterative approach that begins with downsampling of a finite fault model inverted from global seismic records. Direct adjustment of the fault displacement guided by high‐resolution forward modeling of near‐field tsunami waveform and runup measurements improves the features that are not satisfactorily accounted for by the seismic wave inversion. The results show acute sensitivity of the runup to impulsive tsunami waves generated by near‐trench slip. The adjusted finite fault model is able to reproduce the DART records across the Pacific Ocean in forward modeling of the far‐field tsunami as well as the global seismic records through a finer‐scale subfault moment‐ and rake‐constrained inversion, thereby validating its ability to account for the tsunami and teleseismic observations without requiring an exotic source. The upsampled final model gives reasonably good fits to onshore and offshore geodetic observations albeit early after‐slip effects and wedge faulting that cannot be reliably accounted for. The large predicted slip of over 20 m at shallow depth extending northward to ~39.7°N indicates extensive rerupture and reduced seismic hazard of the 1896 tsunami earthquake zone, as inferred to varying extents by several recent joint and tsunami‐only inversions. Key Points: A new fault slip model satisfactorily reproduces global seismic waves, basin‐wide tsunami waveforms, and regional coastal runup Iterative seismic wave inversion and forward tsunami modeling achieve self‐consistency and give reasonable prediction of geodetic data Observed tsunami waveforms and runup heights do not require an exotic source undetected in seismic or geodetic data